Corticospinal Excitability of the Lower Limb Muscles During the Anticipatory Postural Adjustments: A TMS Study During Dart Throwing - Matsumoto, Amiri; Liang, Nan; Ueda, Hajime; Irie, Keisuke (Frontiers in Human Neuroscience, 2021)
Objective: To investigate whether the changes in the corticospinal excitability contribute to the anticipatory postural adjustments (APAs) in the lower limb muscles when performing the ballistic upper limb movement of the dart throwing. Methods: We examined the primary motor cortex (M1) excitability of the lower limb muscles [tibialis anterior (TA) and soleus (SOL) muscles] during the APA phase by using transcranial magnetic stimulation (TMS) in the healthy volunteers. The surface electromyography (EMG) of anterior deltoid, triceps brachii, biceps brachii, TA, and SOL muscles was recorded and the motor evoked potential (MEP) to TMS was recorded in the TA muscle along with the SOL muscle. TMS at the hotspot of the TA muscle was applied at the timings immediately prior to the TA onset. The kinematic parameters including the three-dimensional motion analysis and center of pressure (COP) during the dart throwing were also assessed. Results: The changes in COP and EMG of the TA muscle occurred preceding the dart throwing, which involved a slight elbow flexion followed by an extension. The correlation analysis revealed that the onset of the TA muscle was related to the COP change and the elbow joint flexion. The MEP amplitude in the TA muscle, but not that in the SOL muscle, significantly increased immediately prior to the EMG burst (100, 50, and 0 ms prior to the TA onset). Conclusion: Our findings demonstrate that the corticospinal excitability of the TA muscle increases prior to the ballistic upper limb movement of the dart throwing, suggesting that the corticospinal pathway contributes to the APA in the lower limb in a muscle-specific manner.